2020
DOI: 10.1111/apha.13442
|View full text |Cite
|
Sign up to set email alerts
|

Epac1 null mice have nephrogenic diabetes insipidus with deficient corticopapillary osmotic gradient and weaker collecting duct tight junctions

Abstract: Aim The cAMP‐mediator Epac1 (RapGef3) has high renal expression. Preliminary observations revealed increased diuresis in Epac1−/− mice. We hypothesized that Epac1 could restrict diuresis by promoting transcellular collecting duct (CD) water and urea transport or by stabilizing CD paracellular junctions to reduce osmolyte loss from the renal papillary interstitium. Methods In Epac1−/− and Wt C57BL/6J mice, renal papillae, dissected from snap‐frozen kidneys, were assayed for the content of key osmolytes. Cell ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 46 publications
(86 reference statements)
0
8
0
Order By: Relevance
“…2 Dealing with NDI a study showed that Epac1 −/− (exchange protein directly activated by cAMP) mice had an increased diuresis compared to their wild type littermates. 3 However, some parameters were similar, such as aquaporin 2 expression, albumin permeability and sodium excretion. Differences appeared in responsiveness to AVP, urine composition and altered microvascular permeability within the different genotypes.…”
Section: Renal Failure In Focusmentioning
confidence: 96%
See 3 more Smart Citations
“…2 Dealing with NDI a study showed that Epac1 −/− (exchange protein directly activated by cAMP) mice had an increased diuresis compared to their wild type littermates. 3 However, some parameters were similar, such as aquaporin 2 expression, albumin permeability and sodium excretion. Differences appeared in responsiveness to AVP, urine composition and altered microvascular permeability within the different genotypes.…”
Section: Renal Failure In Focusmentioning
confidence: 96%
“…This led to the conclusion that Epac1 is essential for maintaining the corticomedullary osmotic gradient. 3 Furthermore, tightly regulated sodium excretion is essential for the electrolyte balance. In the nephrotic syndrome (NS) sodium excretion impedes proteinuria.…”
Section: Renal Failure In Focusmentioning
confidence: 99%
See 2 more Smart Citations
“…In most scientific disciplines the standard for the statistical power and the level of significance are 0.8 and 0.05 respectively 15,16 . There are differences between disciplines, and it is common for some scientists to use alpha levels ( P ‐value <alpha) of 0.01 or below or to differentiate between different levels of certainty within one publication 17‐21 . A more detailed guide to finding the correct levels for alpha‐ and beta‐errors and important caveats is available 22 …”
Section: Figurementioning
confidence: 99%